ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN PARIGI MOUTONG - Dahlan, Moh. Ikbal (Katalogis, 2018)
The aim of the study is to determine and analyze the growth of local tax, regional retributions, and local revenues as well as regional tax contributions and local retributions in increasing local revenues in Parigi Moutong Regency. Type of study is descriptive. Informants consist of 8 officials from the office of local revenues, the office of transportation, communication, and informatics, the office of industrial and trade, and the office of agriculture and livestock. The result finds that: 1) realization of regional tax revenues shows an increase during the 5-year budget, but the growth in fluctuating; 2) realization of local revenues increased in fiscal year 2011 to 2013 but decreased significantly in fiscal year 2014-2015 with a negative growth; 3) local revenue continue to increase and the growth is flunctuating; 4) contribution of local tax to increase local revenues shows a downward trend with less criteria.